The Proportion of Orthostatic Hypotension and Its Relationship with HbA1c Levels in Elderly Patients with Diabetes - Catarina Budyono; Siti Setiati; Dyah Purnamasari; Cleopas M Rumende (Acta Medica Indonesiana)
Aim: to obtain information on the proportion of orthostatic hypotension in elderly patients with diabetes and its relationship with HbA1c levels. Methods: this is a cross-sectional study on 350 patients with diabetes mellitus (DM) aged ≥60 years old who sought treatment at outpatient clinic of Geriatry and Diabetes Division at Cipto Mangunkusumo Hospital between January and March 2016. Orthostatic hypotension was defined as a decrease in systolic blood pressure ≥20 mmHg and/or diastolic pressure ≥10 mmHg within 3 minutes after changing position from lying to standing. HbA1c levels was measured using Nycocard from Axis Shield. Chi square test was used for bivariate analysis and logistic regression was used for multivariate analysis against confounding variables. Results: the proportion of orthostatic hypotension in elderly subjects with DM was 27.4%. Median of HbA1c levels was higher in subjects with than without orthostatic hypotension (7.6% vs. 7.1%; p<0.05). There was an association between HbA1c levels of ≥7.35% and the incidence of orthostatic hypotension (OR 1.987, 95% CI 1.2-3.2). The duration of having DM was a confounding variable. Conclusion: orthostatic hypotension is more common in elderly subjects with DM. There is an association between the incidence of orthostatic hypotension and increased HbA1c levels in elderly patients with diabetes mellitus.